Pembinaan Karakter Santri dan Masyarakat di Pondok Pesantren di Kota Banjarbaru Melalui Pendidikan Biologi: Meningkatkan Kesadaran Lingkungan dan Kesehatan - Sari Indriyani; Anwar Hafidzi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to investigate the role of biology education in fostering the character of students and communities in Islamic Boarding Schools in Banjarbaru City. The main focus of the research is on increasing environmental and health awareness through biology learning methods. The research methods used involved surveys, interviews, and observations of students and communities involved in the biology education program at the boarding school. The results showed that character building through biology education has a positive impact on environmental and health awareness. Students and the community became more aware of the importance of protecting the environment and had better knowledge of good health practices. In addition, this study also identified factors that support or hinder the implementation of biology education as a means of character building in a boarding school environment. The findings provide an important contribution to the development of character education in the boarding school environment, particularly through the implementation of biology education as a means to increase environmental and health awareness. The implications of this study can be used as a foundation for the improvement and development of character building programs in boarding schools and also as an inspiration for other educational institutions that want to integrate character values through special subjects such as biology.